Has UTI and Clostridioides difficile Testing and Treatment Stewardship Diffused Into Oregon Hospitals? A Survey of the Current State. (October 2020) - Villamagna, Angela; Pierce, Rebecca; Tran, Dat; Tammer, Roza; Iguchi, Lisa; Zhang, Alexia; Pfeiffer, Christopher
Abstract : Background: Urinary tract infection (UTI) and Clostridioides difficile infection (CDI) both pose significant diagnostic challenges. Excess testing has implications for hospital-associated infection surveillance and may also lead to overtreatment and associated patient risk. Accurate diagnosis requires stewardship efforts to ensure that the correct patients are tested appropriately. In coordination with clinicians and microbiology labs, hospital infection prevention departments can aid diagnostic stewardship efforts by creating policies for order indications and proper test collection methods and by developing electronic medical record (EMR) support for diagnostic and treatment algorithms. The prevalence of these practices in Oregon, however, is unknown. Methods: We deployed a web-based survey to infection preventionists at all 61 acute-care hospitals in Oregon in January 2019. Responses were collected through April 2019, and a subset of applicable questions were analyzed. Results: Of 61 acute-care hospitals, 58 (95%) responded. A response from a single long-term acute-care hospital was excluded. For urinary tract infections (UTIs), a minority of hospitals reported having policies requiring annual sterile urine collection training for registered nurses (n = 7, 12%), annual observation of the RN sterile urine collection procedure (n = 1, 2%), or use of boric acid containers for urine collection (n = 10, 17%). UTI testing and treatment algorithms embedded in the electronic medical record (EMR) were more common (Fig. 1). Regarding urine culture reflex policies, 39 facilities (68%) reported reflexing abnormal urinalyses to culture only if ordered, whereas 14 respondents (25%) reported automatically reflexed all abnormal urinalyses to culture. For Clostridioides difficile infection (CDI), respondents reported using a variety of methods to discourage inappropriate testing (Fig. 2). Although almost all facilities (n = 53, 93%) reported having a policy to reject formed stool, less than half (n = 27, 47%) reported having a policy to reject stool in patients receiving laxatives. Furthermore, 74% of respondents (n = 42) had a published testing algorithm, more than twice the 18 (32%) hospitals that reported having a comparable UTI algorithm. Conclusions: Infection prevention departments in Oregon acute-care hospitals utilize a variety of tools to contribute to diagnostic and treatment stewardship for UTI and CDI. Our survey revealed many opportunities for improvement in UTI and C. difficile testing and treatment stewardship in Oregon hospitals. For example, although most hospitals reject formed stool for CDI testing, policies for other diagnosis and treatment stewardship techniques were much less commonly employed. Future work will compare the results of this survey to a set of similar questions on a statewide microbiology laboratory survey, assess best practices, and form consensus recommendations on stewardship practices for the state. Funding: None Disclosures: None